circ-MYBL2 Serves As A Sponge For miR-361-3p Promoting Cervical Cancer Cells Proliferation And Invasion - Wang J (OncoTargets and Therapy, 2019)
Jinrong Wang,1 Hui Li,2 Zhen Liang3 1OB-Gyn and Pediatrics Department, Medical School, Xijing University, Xi’an, Shaanxi 710123, People’s Republic of China; 2Basic Medicine Department, Nursing School of Zhengzhou Sias University, Xinzheng, Henan 451000, People’s Republic of China; 3Department of Obstetrics and Gynecology, Linfen People’s Hospital, Linfen, Shanxi 041000, People’s Republic of ChinaCorrespondence: Jinrong WangXijing University, No.1 Xijing Road, Chang’an District, Xi’an 710123, Shaanxi, People’s Republic of ChinaEmail wjrhonour@163.comBackground: Circular RNAs (circRNAs) have been considered as a key regulator in tumor carcinogenesis. However, the roles and underlying mechanisms of circRNAs in cervical cancer (CC) remain largely unknown. In this study, we explored the effects of circ-MYBL2 (hsa_circ_0060467) on CC progression.Methods: Levels of circ-MYBL2 and miR-361-3p were examined by qRT-PCR. CCK-8 assay, colony formation assay and transwell invasion assay were used to determine the roles of circ-MYBL2 in CC. Dual-luciferase reporter and RNA pull down assays were employed to verify the relationship between circ-MYBL2 and miR-361-3p.Results: We showed that the expression of circ-MYBL2 was significantly upregulated and positively associated with advanced FIGO stage, larger tumor size, lymph node metastasis, and poor prognosis in CC patients. Function assays revealed that circ-MYBL2 inhibition suppressed CC cells’ proliferation, invasion and epithelial–mesenchymal transition (EMT) processes. In mechanism, miR-361-3p was identified as a direct target of circ-MYBL2, rescue assays showed that miR-361-3p suppression reversed the effects of si-circ-MYBL2 on CC cells’ progression.Conclusion: Our findings suggested that circ-MYBL2 promoted CC progression by regulating miR-361-3p expression, which provided a novel therapeutic target for the treatment of CC patients.Keywords: circ-MYBL2, miR-361-3p, cervical cancer, proliferation, invasion